Penerapan Metode Least Squares Method Dalam Estimasi Penjualan Produk Elektronik - Elentina Sinaga (Journal of Computing and Informatics Research, 2023)
PT. Indotara Persada is a company engaged in the sale of electronic products, where electronic products are one of the people's needs such as fans, magicom, gas stoves, dispensers and so on. This company is experiencing unstable sales, so a decision is needed to overcome this. Unstable sales, the company experiences losses and does not get more profit every month in the future. In forecasting activities, forecasting methods are needed, this is in order to be able to find out in dealing with sales months for the next year to come. For this reason, the researcher uses the Laest Squares method with the aim of helping the company predict sales for the next month, so that if the predicted sales results for the next month decrease, the company will follow up such as doing promotions, giving discounts and so on. The Least Square method is a method in the form of periodic series data or time series, which requires sales data in the past to forecast future sales so that the results can be determined. Least Square is a forecasting method used to see trends from time series data. The Least Square method can be used to determine the equality of data trends which includes Time Series analysis with two cases of even and odd data